Biomechanical and Biochemical Analyses of the Effects of Propranolol on the Osseointegration of Implants - Tekin, Samet; Dundar, Serkan; Demirci, Fatih; Bozoglan, Alihan; Yildirim, Tuba Talo; Karaman, Tahir; Gul, Mehmet (Lippincott Williams & Wilkins, 2021)
This study aimed to investigate the effects of systemic propranolol on the osseointegration of titanium implants. After the surgical insertion of titanium implants into the metaphyseal part of the tibiae of rats, the rats were randomly divided into three equal groups: the control (n = 8), propranolol dosage-1 (PRP-1) (n = 8), and propranolol dosage-2 (PRP-2) (n = 8) groups. In the control group, the rats received no further treatment during the 4-week experimental period after the surgery. After the surgical insertion of the implants, the rats in the PRP-1 and PRP-2 groups were given 5 mg/kg and 10 mg/kg propranolol, respectively, every 3 days for the 4-week experimental period. After the experimental period, the rats were euthanized. Blood sera were collected for biochemical analysis, and the implants and surrounding bone tissues were used for the biomechanical reverse torque analysis. One-way ANOVA and Tukey's honest significant difference test were used for statistical analysis. The student t-test was used to analyze the data obtained from the tests and the controls. There were no significant differences in the reverse torque analysis results and the biochemical parameters (alkaline phosphatase, calcium, and phosphorus) of the groups (P > 0.05). Alkaline phosphatase was, however, found to be higher in test animals compared to the controls (P < 0.05). Also, propranolol did not biomechanically affect the osseointegration of titanium implants, while alkaline phosphatase activity was higher in the test animals.
Keywords: beta- adrenergic receptors; bone implant connection; osseointegration; propranolol; titanium implant